2015
DOI: 10.7727/wimj.2015.385
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin against Formaldehyde-induced Renal Toxicity in Rats

Abstract: Objectives: To explore the protective effects of curcumin against renal injury induced by formaldehyde in rats. Materials and Methods: A total of 21 male Sprague-Dawley rats were included. The animals were divided into three groups. The control group, received 10 ml/kg of physiological saline intragastrically and intraperitoneally on a daily basis. The formaldehyde group were given 10 ml/kg of physiological saline intragastrically plus 10 mg/kg of formaldehyde intraperitoneally. The formaldehyde+curcumin group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Formaldehyde causes lipid peroxidation by reducing the activity of superoxide dismutase and glutathione peroxidase so that the concentration of malondialdehyde increases. [29][30][31] Research in formaldehyde-induced rats was shown to increase malondialdehyde levels. 24 The absence of a significant difference in malondialdehyde levels in this study showed that the administration of Caesalpinia sappan L. extract during the 28 days of intervention has not been able to suppress the lipid peroxidation process caused by inhaled formaldehyde.…”
Section: Effect Of Caesalpinia Sappan L Ethanol Extract On Blood Seru...mentioning
confidence: 99%
“…Formaldehyde causes lipid peroxidation by reducing the activity of superoxide dismutase and glutathione peroxidase so that the concentration of malondialdehyde increases. [29][30][31] Research in formaldehyde-induced rats was shown to increase malondialdehyde levels. 24 The absence of a significant difference in malondialdehyde levels in this study showed that the administration of Caesalpinia sappan L. extract during the 28 days of intervention has not been able to suppress the lipid peroxidation process caused by inhaled formaldehyde.…”
Section: Effect Of Caesalpinia Sappan L Ethanol Extract On Blood Seru...mentioning
confidence: 99%
“…Previous studies showed that compounds, including exogenous FA scavengers (resveratrol, Res [222] ), Curcumin (Cur), [223,224] EGCG, and endogenous FA scavengers (Co‐enzyme Q10 (Q10), [12] melatonin (MT), [225] and glutathione (GSH) [226–228] ), can have spontaneous reactions with FA (Figure 5b). Furthermore, these chemicals have been found to inhibit Aβ oligomerization and fibrillation in vitro , and reduce SP formation, which was associated with improvements in cognition in AD animal models [162,229–234] .…”
Section: New Drug For Targeting Aβ Dimersmentioning
confidence: 99%